Analisis Kualitas Pelayanan Terhadap Kepuasan E-Customer Start-Up Kaos Nyenyes - Agus Yusrizal Bakhrie; Juwita Puja Anggraini; Loren Diaz Lintang; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to analyze the quality of service when shopping and the impact on e-customer satisfaction at Kaos Nyenyes start-up which is a start-up that focuses on selling t-shirts with unique and innovative models online and offline. This research uses qualitative and quantitative analysis methods to gain a comprehensive understanding of how service quality can affect online customer perception and satisfaction. The data collection method involves an online survey of Kaos Nyenyes' e-customers and the collected data is then analyzed using statistical techniques and content analysis to identify the most influential service quality factors. The results of this study are expected to provide deep insights into the aspects and factors of service quality that are important in a business context, especially in the fashion industry such as the Kaos Nyenyes start-up. By understanding the factors that influence customer satisfaction, companies can improve service strategies, strengthen relationships, and increase competitive advantage in the market.